Fishing of α-Glucosidase’s Ligands from Aloe vera by α-Glucosidase Functionalized Magnetic Nanoparticles - Hao Yuan; Hong Wan; Yi-Kao Hu; Emmanuel Ayodeji Ayeni; Qiang Chang; Chao Ma; Xun Liao (Molecules, 2021)
α-Glucosidase was immobilized on magnetic nanoparticles (MNPs) for selective solid-phase extraction of the enzyme’s ligands present in Aloe vera, which is a medicinal plant used for the treatment of various diseases and possesses anti-diabetic activity. One new compound, aloeacone (2), together with two known compounds, aloenin aglycone (1) and aloin A (3), were fished out as the enzyme’s ligands. The structure of 2 was determined by HR-MS and comprehensive NMR techniques. Compound 3 exhibited a weak inhibitory effect on α-glucosidase, while compounds 1 and 2 were found to possess activation effects on the enzyme for the first time. It is interesting that both an inhibitor and agonists of α-glucosidase were fished out in one experiment.